Utility of the transcervical approach in bilateral synchronous lung cancer. (October 2015) - Obiols, Carme; Call, Sergi; Rami-Porta, Ramón; Trujillo-Reyes, Juan Carlos
Bilateral pulmonary nodules represent a challenge in distinguishing between synchronous bronchogenic carcinomas and metastatic disease. In the case of potentially curable synchronous lung cancer, it is recommended to treat each lesion with curative intent if there is no evidence of mediastinal involvement or extrathoracic disease. In this situation, surgical staging of the mediastinum is recommended. This case shows the utility of a transcervical approach to perform precise mediastinal staging and lymphadenectomy, and to access the pleural cavity to resect a pulmonary nodule. Moreover, video-assisted mediastinoscopic lymphadenectomy combined with video-assisted lobectomy could be a good option for a radical lymphadenectomy.